Trends and Developments in Research on the Transition from Preschool to Primary School: A Bibliometric Analysis - Anisaturrahmi Anisaturrahmi; Mohd Syaubari Othman; Rosmiati Rosmiati; Mutia Sari; Muh Khairul Wajedi Imami (Universitas Negeri Padang, 2026)
The transition from preschool to primary school is a critical time for students, as they must adjust from the play-based learning approach in preschool to the more structured and curriculum-focused education of primary school. However, bibliometric analysis in this topic is scare. Therefore, the current bibliometric analysis investigates the evolution of research on the school transition from preschool to primary school, focussing on significant findings on author contributions, country-based production, and institutional engagement. According to the study, Petriwskyj has the most publications in the field, and author collaboration networks are organised into various groups. Research output varies over time, with some authors making constant contributions and achieving higher citation impact, while others have intermittent or limited scholarly effect. The United States leads in research output, followed by Finland, Turkey, and Australia, with rising contributors such as China and Greece gaining traction. Citation impact is particularly high in the United States and Finland, indicating differences in research contributions between countries. According to affiliation analysis, the University of Jyväskylä is the highest-rated institution, followed by Queensland University of Technology and the University of North Carolina. The production trends show that the National Council for Curriculum and Assessment (NCCA) will increase its research activities significantly beginning in 2021, while other leading universities such as the University of Jyväskylä and the University of Kentucky continue to increase their research output. This study gives a comprehensive overview of the changing landscape of research on preschool-to-primary school transition, emphasising the academic field's dynamic and collaborative nature.